Effect of Ecoenzim Solution on Balsam Plant (Impatiens balsamina L.) Growth - Ratna Dewi Eskundari; Suwaji Handaru Wardoyo; Fiky Ariska Cahyanti; Rindi Diah Ayu Fitriani; Dian Andhi Saputra (Jurnal Biologi Tropis, 2023)
Balsam plant is widely known as plants with a myriad of benefits. This plant includes plants that are easily propagated and cared for. However, plant maintenance will be important to ensure the continued growth and development of these plants. One of the environmentally friendly liquid organic fertilizers is ecoenzyme. Ecoenzyme is widely recognized as a multipurpose solution made from fermented sugar with vegetable and or fruit residue. This study aims to determine the effect of ecoenzyme solutions on the growth of Impatiens balsamina L. plants. This study followed a completely randomized design (CRD) with one factor. The data obtained were then analyzed by means of analysis of variance (ANOVA) in a one-factor completely randomized design and followed by the Duncan Multiple Range Test (DMRT) with a 95% confidence level. The results showed that on the parameters of leaf and stem length, watering with the addition of ecoenzyme had a significant effect on the growth of balsam plants starting at 30-day after culturing (DAC) and 51-DAC. Anatomical analysis of the root, stem and leaf of balsam plant treated with watering using the addition of ecoenzyme solution showed that there were significant differences with the control. The results of this study are expected to increase knowledge related to the propagation of balsam plants and the use of ecoenzyme as liquid organic fertilizer.